Access to homeownership in decline—rising housing inequalities for young people in the neoliberal housing market of Tallinn - Kährik, Anneli; Pastak, Ingmar (Frontiers in Sustainable Cities, 2023)
The current housing affordability crisis, driven mainly by the financialization of housing and the government's retrenchment of social policies and provision of affordable housing, have affected growing inequalities in access to housing. The crises have hit young people especially hard. The recent trends call for systematic studies on the mechanisms generating such intergenerational inequality, considering the specifics of the prevailing housing regimes. Housing affordability in Tallinn has decreased due to fast-growing housing prices, as a result of an ultra-liberal housing regime, exemplified by housing financialization, capital accumulation, low level of governmental interventions and an overall increase in social inequalities. Based on EU-SILC data, it is shown how the recent trends during the decade between 2010 and 2020 have negatively impacted young people's access to homeownership—access has been greatly reduced for young cohorts, and it has become more differentiated, based on the socio-economic and labor market performance of households, as well as intergenerational transfers. Young households are increasingly residing in private rental dwellings, and many still rely on parental housing until their 30s. Rental housing, as compared to homeownership, has fewer advantages compared to homeownership—it brings no capital gains and is less secure, and rental stock tends to be located unevenly across urban space and to be in slightly worse condition compared to owner-occupied housing. This positions young people in an unfavorable position in the perspective of their housing career, and this can have severe consequences on their social inclusion.